High throughput chromatography strategies for potential use in the formal process characterization of a monoclonal antibody. Issue 6 (31st December 2015) - Petroff, Matthew G.; Bao, Haiying; Welsh, John P.; van Beuningen – de Vaan, Miranda; Pollard, Jennifer M.; Roush, David J.; Kandula, Sunitha; Machielsen, Peter; Tugcu, Nihal; Linden, Thomas O.
ABSTRACT: High throughput experimental strategies are central to the rapid optimization of biologics purification processes. In this work, we extend common high throughput technologies towards the characterization of a multi‐column chromatography process for a monoclonal antibody (mAb). Scale‐down strategies were first evaluated by comparing breakthrough, retention, and performance (yields and clearance of aggregates and host cell protein) across miniature and lab scale columns. The process operating space was then evaluated using several integrated formats, with batch experimentation to define process testing ranges, miniature columns to evaluate the operating space, and comparison to traditional scale columns to establish scale‐up correlations and verify the determined operating space. When compared to an independent characterization study at traditional lab column scale, the high throughput approach identified the same control parameters and similar process sensitivity. Importantly, the high throughput approach significantly decreased time and material needs while improving prediction robustness. Miniature columns and manufacturing scale centerpoint data comparisons support the validity of this approach, making the high throughput strategy an attractive and appropriate scale‐down tool for the formal characterization of biotherapeutic processes in the future if regulatory acceptance of the miniature column data can be achieved. Biotechnol. Bioeng. 2016;113: 1273–1283. © 2015 Wiley Periodicals, Inc. Abstract : A comparison of miniature column and traditional lab scale column process characterization for a monoclonal antibody indicates similar model performance and sensitivity to process parameters. Miniature column centerpoint operating conditions are also in line with both traditional lab scale columns as well as full scale manufacturing columns.